Kontribusi Madrasah Diniyah Takmiliyah Sebagai Penyempurna Mata Pelajaran Pendidikan Agama Islam di Sekolah Formal - Suryana (Kantor Kementerian Agama Kabupaten Pangandaran bekerja sama dengan Asosiasi Profesi Perkumpulan Manajer Pendidikan Islam (Perma Pendis) Indonesia., 2021)
Faith, piety, and noble character are at the core of Indonesia's National Instruction Goals, which are realized in schools through Islamic religious education (PAI). However, Islamic religious education in formal schools receives a very little amount of instructional time, ranging from 2 (two) to 5 (five) hours each week. PAI learning is not optimal due to the limited number of training hours. Madrasah Diniyah Takmiliyah as a non-formal educational institution is a solution to deepen and expand Islamic religious education materials in formal schools. The portion of the lesson hours that reaches 18 hours a week and its peculiarities which increase the practice of worship activities provide opportunities for students to deepen and expand their knowledge and practice of Islamic worship. PAI learning activities in madrasah diniyah have a strategic role and function, namely improving the achievement of competency standards for PAI subjects, which include aspects of knowledge, attitudes, and skills.